Pengembangan Aplikasi Pembelajaran Permainan Tenis Meja Berbasis Android : Android-Based Table Tennis Game Learning Application Development - Bimo, Pandu Arroyo (Jurnal IKA, 2025)
The aim of this research is to develop an Android-based table tennis learning application for students in the Health and Recreation Physical Education study program for the 2023/2024 academic year. The increasing use of technology, especially smartphones, provides a great opportunity to integrate technology into education. In this context, the application of table tennis learning is expected to make it easier for students to acquire basic techniques and theoretical knowledge of the game in a more interactive and flexible manner. The research method used is research and development using the ADDIE model (analysis, design, development, implementation, and evaluation). The results of the development are Android-based applications, including historical material, facilities and infrastructure, basic techniques and game rules, as well as quizzes for evaluating theory and practice. Product validation is carried out by content and material experts, media experts, design experts and field practitioners. The assessment results show a validity percentage of 96% from content experts, 100% from media experts, 90% from design experts, and 100% from field practitioners, all in the "Very Good" category. Application trials also showed a positive response from students, with individual trials and small group trials reaching 99% and 100%, respectively, while field trials received an average score of 45 and a percentage of 89% with "good" criteria. The conclusion of this research is that this Android-based table tennis learning application is suitable for use in learning the game of table tennis.